Efficacy of different amniotic membrane transplantation techniques in patients with inflammatory and degenerative pathology of the cornea - Sereda, E. V.; Drozhzhina, G. I.; Gaidamaka, T. B.; Ivanovskaia, E.V.; Ostashevskii, V.L.; Ivanova, O.N.; Kogan, B.M. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Due to its unique properties, amniotic membrane transplantation took its place in reconstructive surgery of ocular surface. The standard technique for amniotic membrane transplantation does not exist. Purpose. To compare the efficacy of different amniotic membrane transplantation techniques in patients with inflammatory and degenerative pathology of the cornea, according to archival patient's cases. Material and Methods. The analysis of 65 archival patient's cases, who underwent amniotic membrane transplantation was made. Three amniotic membrane transplantation technique were used: inlay (graft transplantation), onlay (biological covering), sandwich (combined technique). After the operation, a bandage soft contact lens was put on the corneal surface with fixed amniotic membrane. In the case of amniotic membrane transplantation combined with blepharorrhaphy contact lens was not used. Results. Our study showed high efficacy of amniotic membrane transplantation in patients with different pathologies of the cornea (recurrent pterygium, bullous form of endothelial-epithelial corneal dystrophy), keratitis (bacterial, neurotrophic, autoimmune and herpetic) and corneal burns. In 62 patients (95.4%), positive therapeutic effect was obtained with corneal epithelialization activation, elimination of inflammation and pain, and the absence of pterygium recurrences. It was found that among the patients who had underwent an inlay-technique of amniotic membrane transplantation, the highest efficacy was noted in patients with herpetic and bacterial ulcers. In the group of patients undergone an onlay-technique, the highest efficacy was noted in patients with endothelial-epithelial corneal dystrophy and neurotrophic keratitis and in patients with a sandwich-technique, the highest efficacy was in patients with autoimmune corneal ulcers. Conclusions. There is no one opinion about the best surgical technique of amniotic membrane transplantation. That's why the pilot study on the amniotic membrane transplantation efficacy and the effect on the course of inflammation in the corneal tissue depending on type of its fixation is of scientific and practical interest.